Impact of Corporate Social Responsibility on Corporate Governance and Reputation in Nepalese Commercial Banks - Chalise, Mahananda (Journal of Development and Administrative Studies, 2015)
Corporate social responsibility (CSR) has been the subject of considerable investigation and debate for many years among both scholars and practitioners. Corporate social responsibility (CSR), corporate governance (CG) and corporate reputation (CR) influence the development of firms mostly. In this paper, a model of dynamic relations among CSR, corporate governance and corporate reputation was constructed in the theoretical framework of stakeholder. The model reflects that corporate reputation is formed in the dynamic relations between firms and corporate stakeholders, and corporate reputation is the synthesized result of corporate governance and CSR. For the purpose of testing the fitness of the model in Nepal, an empirical study is conducted on the relationship between corporate governance, CSR and corporate reputation. The result shows that good CSR has positive effect on banks reputation. It also indicates that CG and CR don't have significant relationship, but coefficient of the intervariable (CG*CSR) is significant and positive, which reflects that good corporate governance alone can't bring good reputation, but it can't when it comes with good social responsibility. The Journal of Development and Administrative Studies, Vol. 22, No. 1-2, pp. 27-36, 2014